Vitamin D3 and calcium cosupplementation alleviates cadmium hepatotoxicity in the rat: Enhanced antioxidative and anti‐inflammatory actions by remodeling cellular calcium pathways. Issue 3 (11th January 2020) - El‐Boshy, Mohamed; Refaat, Bassem; Almaimani, Riyad A.; Abdelghany, Abdelghany H.; Ahmad, Jawwad; Idris, Shakir; Almasmoum, Hussain; Mahbub, Amani A.; Ghaith, Mazen M.; BaSalamah, Mohammad A.
Abstract: Although vitamin D (VD) and calcium (Ca) attenuate cadmium (Cd) metabolism, their combined antioxidant and anti‐inflammatory actions against Cd toxicity have not been previously explored. Hence, this study measured the protective effects of VD ± Ca supplements against Cd hepatotoxicity. Forty adult male rats were distributed to: negative controls (NCs), positive controls (PCs), VD, Ca, and VD3 and Ca (VDC) groups. All groups, except NC, received CdCl2 in drinking water (44 mg/L) for 4 weeks individually or concurrently with intramuscular VD3 (600 IU/kg; three times per week) and/or oral Ca (100 mg/kg; five times per week). The PC group showed abnormal hepatic biochemical parameters and increase in cellular cytochrome C, caspase‐9, and caspase‐3 alongside the apoptotic/necrotic cell numbers by terminal deoxynucleotidyl transferase dUTP nick end labeling technique. The PC hepatic tissue also had substantially elevated pro‐oxidants (malondialdehyde [MDA]/H2 O2 /protein carbonyls) and inflammatory cytokines (interleukin 1β [IL‐1β]/IL‐6/IL17A/tumor necrosis factor‐α), whereas the anti‐inflammatory (IL‐10/IL‐22) and antioxidants (glutathione [GSH]/GPx/catalase enzyme [CAT]) markers declined. Hypovitaminosis D, low hepatic tissue Ca, aberrant hepatic expression of VD‐metabolizing enzymes (Cyp2R1/Cyp27a1/cyp24a1), receptor and binding protein alongside Ca‐membrane (CaV 1.1/CaV 3.1), and store‐operated (RyR1/ITPR1) channels, and Ca‐binding proteins (CAM/CAMKIIA/S100A1/S100B) were observed in the PC group. Both monotherapies decreased serum, but not tissue Cd levels, restored the targeted hepatic VD/Ca molecules' expression. However, these effects were more prominent in the VD group than the Ca group. The VDC group, contrariwise, disclosed the greatest alleviations on serum and tissue Cd, inflammatory and oxidative markers, the VD/Ca molecules and tissue integrity. In conclusion, this report is the first to reveal boosted protection for cosupplementing VD and Ca against Cd hepatotoxicity that could be due to enhanced antioxidative, anti‐inflammatory, and modulation of the Ca pathways.